1981
DOI: 10.1159/000172825
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Sieve in Rat Tubular Basement Membrane as Revealed by Negative Staining

Abstract: Rat tubuli were isolated both by the method of Krisko and by a modified method of Cook and Pickering; renal tubular basement membrane (TBM) was isolated by sonic disruption and by the method of Carlson. Using electron microscopy after negative staining, TBM of rat kidney isolated under these different conditions was shown to be a fine meshwork. Strands of the meshwork were interwoven, apparently enclosing pores to make up whole basement membrane. These findings are compared with our previous observation that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…The present findings obtained with HSEM confirm our previous study showing that the BM is a molecular sieve composed of pores and strands [9][10][11], The meshwork structure was not an artifact of the isolation procedure because similar meshwork structures 197 were observed in BMs isolated by two different procedures; we observed a similar meshwork structure using HSEM in untreated GBM specimens [Hironaka et al, unpubl. data].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present findings obtained with HSEM confirm our previous study showing that the BM is a molecular sieve composed of pores and strands [9][10][11], The meshwork structure was not an artifact of the isolation procedure because similar meshwork structures 197 were observed in BMs isolated by two different procedures; we observed a similar meshwork structure using HSEM in untreated GBM specimens [Hironaka et al, unpubl. data].…”
Section: Discussionsupporting
confidence: 90%
“…We found that the meshwork structure was looser in the TBM than in the GBM in previous studies using negative staining and TEM [11,31]. A heterogeneous mesh structure was also observed in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…The presence of pores in the GBM has been postulated from physiological studies [I] and demonstrated by transmission electron microscopy (TEM) by us [2][3] and others [4][5][6], Although scanning electron microscopy (SEM) has an advantage over TEM in that topographical dissimilarity can be observed three-dimensionally, it failed to demonstrate the presence of pores in the GBM.In 1985, a new type of SEM, the ultrahighresolution SEM (HSEM), was developed by Tanaka et al [7]. It is equipped with a field emission source and an objective lens of very short focal length, and has a resolving power of 0.5 nm at 30 kV.…”
mentioning
confidence: 99%
“…On electron microscopy, a lam ina rara externa is separated by the lamina densa from the lamina rara interna. The pores of the glomerular basement mem brane can be made visible showing the di mensions of 1 nanometer range [7]. Its func tional properties are the regulation of filtra tion and to serve as a scaffold.…”
mentioning
confidence: 99%